Secure File Sharing in Multi-clouds using Shamir’s Secret Sharing Scheme - Althamary, Ibrahim Abdullah; Alkharobi, Talal Mousa (Discoveries in Agriculture and Food Sciences, 2016)
Cloud computing is a significant model for permitting on-demand network access to shared data, software’s, infrastructure, and platform resources. However, cloud storage needs a certain level of availability, confidentiality, and integrity. Information sensitivity and value encourage users to select a highly secure protocol. This work proposes a new mechanism to increase the user trust in cloud computing using the secret sharing technique. The proposed algorithm is using Base64 encoding to convert any file type to ASCII strings. Base64 strings do not need any extra process to be compressed and this can speed up the share building process. Each string is used to produce N shares (using Shamir Secret Sharing Scheme) where each share is stored in a separate location in the cloud.